2011
DOI: 10.2341/09-381-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Desensitizing Agents on the Microtensile Bond Strength of a Two-step Self-etch Adhesive to Dentin

Abstract: The aim of this in vitro study was to evaluate the effect of cervical hypersensitivity treatments (neodymium yttrium aluminum garnet [Nd:YAG] laser and conventional techniques) on the microtensile bond strengths of adhesives to treated dentin. The buccal cervical enamel of 42 freshly extracted human mandibular third molars was ground flat to expose the cervical dentin. The dentin surfaces were polished with a series of silicon carbide papers, and the smear was removed with an ethylenediamine tetra-acetic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 26 publications
6
23
0
6
Order By: Relevance
“…A previous study that tested the microtensile bond strength between self-etching and total-etching adhesives in dentin treated with fluoride gel obtained results lower than the control group (any treatment). 27 The authors observed a distortion in hybrid layer by SEM images, fact that could be related to lower bond strength, agreeing with the present study. 27 Infiltration of adhesive systems between dentin collagen fibers, if performed correctly, promotes sealing of dentin tubules.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A previous study that tested the microtensile bond strength between self-etching and total-etching adhesives in dentin treated with fluoride gel obtained results lower than the control group (any treatment). 27 The authors observed a distortion in hybrid layer by SEM images, fact that could be related to lower bond strength, agreeing with the present study. 27 Infiltration of adhesive systems between dentin collagen fibers, if performed correctly, promotes sealing of dentin tubules.…”
Section: Discussionsupporting
confidence: 93%
“…27 The authors observed a distortion in hybrid layer by SEM images, fact that could be related to lower bond strength, agreeing with the present study. 27 Infiltration of adhesive systems between dentin collagen fibers, if performed correctly, promotes sealing of dentin tubules. [27][28][29] The AD group when associated to MS resin cement (Variolink II) showed 8.35 MPa mean SBS and 37.5% of cohesive failures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ancak, bu ajanların adeziv rezinlerin bağlanma dayanımına etkisiyle ilgili literatürde çelişkili sonuçlar vardır. 6,7,8,9 Çalışmamızın amacı; dentin hassasiyetinde kullanılan iki farklı preparatın adeziv simantasyondaki bağlantıya etkisinin karşılaştırılmalı olarak in vitro incelenmesidir. …”
Section: Introductionunclassified
“…Potassium fluoride (KF) is one of the F ‐ compounds used in dentin adhesives and dentin desensitizing agents . Hence, this study aimed to investigate the use of KF on the inhibition of the dentin matrix‐bound MMPs and CCs in order to improve the stability of demineralized dentin matrices.…”
mentioning
confidence: 99%